Minority Voices In Power Rangers Movie: A Study of Popular Literature (NOBEL: Journal of Literature and Language Teaching, 2018)
Power Rangers is a 2017 superhero movie that was previously known in Power Rangers film series. Power Rangers attracts consumers of all ages and backgrounds, and it quickly becomes the box office in the world. This movie gets some critics and controversial responds. The urgency of this study is to respond the controversial issues toward the movie considered harmful for children. My aim to have this study is to expose some important issues which relate to minority groups. The study ascertains minority voices perceived as right equality issue despite many negative issues lingering this movie. This issue links to liberties which include freedom of life stated in US Bill of Human Right. This study applies popular literature approach and Hall representation theory. Research result shows the minority voice that reveals the positive image of minority group such as the powerful and independent individual. It also portrays, courage, confidence, humanities, cares and love, friendship and team working, trust and support, justice and anti-bullying. Those issues are gathered in the scenes from the image: the acceptance of color people and the right of LGBT represented by some characters.